The Role of Entrepreneurship Training and Technological Innovation Adaptation in Improving the Welfare of MSME Actors (Case Study: Bluru Kidul Village, Sidoarjo Regency) - Putri, Amanda Diva Mia; Sishadiyati (Journal of Regional Economics and Development, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in Indonesia’s economy as both employment providers and drivers of community welfare. However, limited entrepreneurial skills and slow technology adoption remain major challenges, including in Bluru Kidul Village, Sidoarjo Regency. This study aims to examine the effect of entrepreneurship training and technological innovation adaptation on the welfare of MSME actors. A quantitative method was employed using multiple linear regression analysis based on survey data from 83 respondents. The findings indicate that entrepreneurship training and innovation adaptation have a positive and significant effect on MSME welfare, measured through business income, sales volume, operational cost efficiency, and household consumption. These results reinforce Amartya Sen’s Capability Approach, which emphasizes expanding individual capabilities through training and technology. Practically, the study provides insights for local governments and support institutions to design MSME empowerment programs that are more adaptive, sustainable, and tailored to the specific needs of local entrepreneurs.